208 Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma (CLL/SLL) With Complex Karyotype, Clinic-Pathological Study and Risk for Richter Transformation. (11th January 2018) - Asad, Romana; Lu, Xinyan; Badar, Ifra; Thakral, Beenu; Priyanka, Priyanka; Muzzafar, Tariq
Abstract: Introduction: Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is a lymphoid neoplasm of with heterogeneous cytogenetic and molecular abnormalities that are used for prognostication. We aimed to do a clinic-pathological study of CLL/SLL with complex karyotype (≥3 abnormalities) and assess risk of Richter transformation. Methods: We identified 333 patients with CLL/SLL having complex karyotype at a single institution from January 1969 to December 31, 2015. Clinicopathological parameters were extracted from institutional databases. Logistic regression (SAS 9.4) was applied to test association between parameters and transformation. Results: Median age was 64 years. Patients included 250 men (75.01%) and 83 women (83%). Laboratory parameters were as follows (median [range]): Hb 11.1 (9.6–12.7) g/dL, WBC 20.6 (7.2–70.9) K/uL, platelets 100 (50–160) K/uL, absolute lymphocyte count 14.96 (3.93–61.11) K/uL, LDH 698 (547–939) IU/L, B2 microglobulin 4.7 (3.2–6.6). Splenomegaly was present in 97 (29.13%) patients, bulky lymphadenopathy in 20 (6.01%). In patients that had results available, CLL cells were positive for ZAP70 in 71% and CD38 in 182 (64.76%) patients. VH mutation was present in 42 (14%). Cytogenetic abnormalities were as follows: -17 in 20 (5.70%), trisomy 12 in 56 (16.82%). A total of 39 patients developed Richter transformation; of these 24 (61.54%) were men and 15(38.46%) women, and median age at time of transformation was 59.5 years. Of 31 patients with survival data, median survival time for Richter transformation was 6.91 years as compared to 7.9 years for 147 subjects without. Only Hb was associated with increased risk of developing Richter transformation. Conclusion: CLL/SLL with complex karyotype is a heterogeneous disease at the genetic level. Only Hb was associated with risk for Richter transformation.